ANALYSIS OF THE EFFECTIVENESS OF JOINT HYDROGRAPHIC SURVEY INDONESIA - SINGAPORE - MALAYSIA TO ENHANCE SAFETY NAVIGATION IN THE STRAIT OF MALACCA AND SINGAPORE - Rechar, Janjan; Jantarto, Dwi; Syaiful, Abdiyan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2020)
The purpose of the Joint Hydrographic Survey (JHS) implementation in Straits of Malacca and Singapore (SOMS) is to improve navigation safety in TSS by using Multibeam EchosounderÂ (MBES) technology. This is especially important given the increasing number of ships carrying out cross-transit through SOMS from year to year, while hydrographic information has not been updated since 1998. This study aims to analyze the effectiveness of JHS activities at SOMS conducted by Indonesia, Malaysia, and Singaporerelated to Indonesia's interests,Â specifications, and procedures, as well as the use of force in JHS activities. This study uses qualitative methods with an exploratory approach and used the NVivo Plus 12 application to find themes from field interviews and used the Soft System Methodology (SSM). Based on the results of the study can be concluded that the effectiveness of JHS activities has been following what is expected by the three coastal countries, but the Indonesian Navy Hydrographic and Oceanography Center or Pusat Hidrografi dan Oseanografi TNI AL (Pushidrosal) as a learning organization is required to continue to be able to improve its capabilities in the implementation of JHS. From the gap of research results obtained several activities that can be carried out by Pushidrosal to increase the effectiveness of JHS in SOMS namely by evaluating the implementation of Security Officer (SO) and Technical Officer (TO) as well as preparing SOP that can be used as a standard in the implementation of JHS activities